Frog and toad together. - Lobel, Arnold; Juvenile Collection (Library of Congress) (New York, Harper & Row, 1972)
Five further adventures of two best friends as they share cookies, plant a garden, and test their bravery.
F
b
b
Keywords: Friendship -- Fiction